Genetic characteristics and strain types of the invasive fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in Indonesia - ANIK BUDHI DHARMAYANTHI; VANI NUR OKTAVIANY SUBAGYO; R. TAUFIQ PURNA NUGRAHA; RAHMINI RAHMINI; CAHYO RAHMADI; DARMAWAN DARMAWAN; HARI SUTRISNO (Society for Indonesian Biodiversity, 2022)
Abstract. Dharmayanthi AB, Subagyo VNO, Nugraha RTP, Rahmini, Rahmadi C, Darmawan, Sutrisno H. 2022. Genetic characteristics and strain types of the invasive fall armyworm Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) in Indonesia. Biodiversitas 23: 3928-3935. The fall armyworm, Spodoptera frugiperda is an invasive pest in the tropical region of the western hemisphere, which is globally distributed, including in Indonesia. Therefore, this study aims to elucidate the genetic characteristics and strain types of the Indonesian population, based on mitochondrial and nuclear gene sequences. The haplotype diversity and phylogenetic trees were assessed according to the COI and COII gene sequences, where 381 bp of Tpi nuclear gene sequences were evaluated to define the strain types. The two haplotypes detected were within COI and COII, while the maximum likelihood tree based on COI gene sequences shows two clades related to rice and corn strain. Tpi gene sequences indicated that the populations belong to the corn strain, which suggested COI as a promising marker when complex inter-strain hybridization has not occurred. It was also discovered that mitochondrial and nuclear markers are inconsistent to define the strains.